Legitimacy and effectiveness of the International Criminal Court (ICC): critical perspectives - Mukhamedzhanova, D.; Raisova, G. (Право и государство, 2016)
The number of violations of international humanitarian law's norms had become an increasing phenomenon. The situation requires urgent and effective international control and prosecution in international tribunals for grave crimes presenting a real threat to security and peace. In order to control such crimes, the relevant legal mechanisms for international prosecution were established through the creation of International Criminal Tribunal for former Yugoslavia (ICTY) and International Criminal Tribunal for Rwanda (ICTR). However, the long court delays and high operational expenses of these tribunals led to the establishment of International Criminal Court (ICC). This article will critically assess the perspectives of the ICC in terms of its legitimacy and effectiveness in comparison with the ICTY and ICTR.
Keywords: International criminal law; International Criminal Tribunal for former Yugoslavia (ICTY); International Criminal Tribunal for Rwanda (ICTR); International Criminal Court (ICC); genocide; crimes against humanity; war crimes; legitimacy; Central African Republic (CAR); Research Subject Categories::LAW/JURISPRUDENCE